Dung beetle assemblages in lowland forests of Pangandaran Nature Reserve, West Java, Indonesia - Windra Priawandiputra; Yamato Tsuji; Kanthi Arum Widayati; Bambang Suryobroto (Society for Indonesian Biodiversity, 2020)
Abstract. Priawandiputra W, Tsuji Y, Widayati KA, Suryobroto B. 2020. Dung beetle assemblages in lowland forests of Pangandaran Nature Reserve, West Java, Indonesia. Biodiversitas 21: 497-504. Dung beetles play crucial role in forest ecosystem, but no information on the dung beetle fauna has been reported in lowland forest of Java Island, Indonesia. Pangandaran Nature Reserve (PNR) area, which is recognized as lowland habitat of wildlife, can also support diversity of dung beetles. This study was conducted to examine the dung beetle diversity in lowland forests of PNR. The dung beetles were collected using pitfall traps baited with five species of mammal’s feces and hand collection of beetles found on dung along the road, between 2016 and 2018. During the study, 853 individuals of dung beetles from 17 species were collected. The dominant species were Onthophagus babirussa with 434 individuals (50.8%). The species were not dominant in the mountainous forests of West Java and in lowland forests of Southeast Sulawesi and East Kalimantan. The highest dung beetle abundances were found during the dry season (August): 335 individuals in 2017 and 286 in 2018. However, the diversity index value of dung beetles in this study was lower in the dry season than in the wet season (t-test of diversity index, P<0.05). The dung beetle assemblages in PNR were barely similar to most dung beetle studies of other regions.